2020
DOI: 10.3390/ijms22010363
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation-Induced Protein Unfolding in Airway Smooth Muscle Triggers a Homeostatic Response in Mitochondria

Abstract: The effects of airway inflammation on airway smooth muscle (ASM) are mediated by pro-inflammatory cytokines such as tumor necrosis factor alpha (TNFα). In this review article, we will provide a unifying hypothesis for a homeostatic response to airway inflammation that mitigates oxidative stress and thereby provides resilience to ASM. Previous studies have shown that acute exposure to TNFα increases ASM force generation in response to muscarinic stimulation (hyper-reactivity) resulting in increased ATP consumpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 75 publications
(106 reference statements)
0
8
0
Order By: Relevance
“…Thus, TNFα increases metabolic demand, which appears to trigger a homeostatic response to increase ATP production by promoting mitochondrial biogenesis and mitochondrial volume density in hASM cells. In addition, by increasing mitochondrial volume density, the demand for ATP production and oxygen consumption per mitochondrion is reduced, thus limiting reactive oxygen species (ROS)-induced oxidative stress [ 9 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, TNFα increases metabolic demand, which appears to trigger a homeostatic response to increase ATP production by promoting mitochondrial biogenesis and mitochondrial volume density in hASM cells. In addition, by increasing mitochondrial volume density, the demand for ATP production and oxygen consumption per mitochondrion is reduced, thus limiting reactive oxygen species (ROS)-induced oxidative stress [ 9 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Airway inflammation is one of the major contributors to the pathophysiology of airway diseases including asthma [ 1 , 2 ], chronic obstructive pulmonary disease (COPD) [ 3 , 4 ], chronic bronchitis [ 5 ], and COVID-19 [ 6 , 7 , 8 ]. Previous studies, including those from our laboratory, have shown that acute exposure to proinflammatory cytokines such as TNFα results in airway smooth muscle (ASM) hyperreactivity in response to agonist stimulation, leading to energetic stress [ 9 , 10 ]. In addition, TNFα induces the proliferation of ASM cells, which also increases energy demand [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…324,325 • Inflammation: Inflammatory stimuli can promote mitochondrial fragmentation by increased protein unfolding, ER stress, phosphorylation of pro-fission proteins, and decreased respiratory capacity. [326][327][328][329][330] There is also increased oxidative stress; mitochondrial complex III generates superoxide during the ubiquinone (Q)-cycle. 331 Some lesions may show mitochondrial fission, mitophagy, and decreased fusion.…”
Section: Epidemiology and Clinical Featuresmentioning
confidence: 99%
“…In addition, nicotinamide riboside, a precursor of NAD + , can activate UPR mt , accompanied by a significant increase in the level of UPR mt -related proteins [ 22 , 23 ]. In airway smooth muscle, inflammation-induced accumulation of ROS and overload of damaged proteins activate the UPR mt , and the proinflammatory cytokine TNF-α plays a crucial role in this event [ 24 ]. Moreover, caloric restriction can activate the UPR mt to improve mitochondrial function, and miRNAs are involved as key mediators [ 25 ].…”
Section: Inducers Of the Upr Mtmentioning
confidence: 99%